PENINGKATAN KEMAMPUAN BERBICARA DAN MOTIVASI MELALUI PENGAJARAN BERBASIS LINGKUNGAN BAGI PESERTA DIDIK KELAS V MIN PUNGGUNG LADING PARIAMAN SELATAN - INDAH SURYA PUTRI; Neviyarni Neviyarni; Irdamurni Irdamurni (Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2019)
This research is motivated by the problems found in Speaking Learning in class V MIN Punggung Lading Pariaman Selatan that there are still many students who have difficulty speaking. The use of regional languages is still often used, the intonation is inaccurate so students are less interested in participating in learning Indonesian especially speaking skills. Therefore an effort to improve speaking skills was carried out through environment-based teaching in class V MIN students in South Pariaman Lading. This research was conducted in the second semester of the 2013/2014 school year for three months, at MIN Punggung Lading Pariaman Selatan. This type of research is Class Action Research (CAR). The research subjects were 18 students in class V. This study was conducted in two cycles, namely cycle I and cycle II. The process of this research goes through four stages, namely: planning, implementation, observation, and reflection. The collected data is analyzed quantitatively, by drawing conclusions. (1) speaking activities of students in class V MIN in the back of South Pariaman Lading in the first cycle reached 65% while in the second cycle reached 82.5%. This shows an increase of 17.5%. (2) Percentage of speaking ability of students in class V MIN in the back of South Pariaman Lading in choosing words, statement of speech, and voice intonation increased from cycle I to cycle II, from 38.9% to 94.4% with 55.5% increase in percentage. Based on the analysis of the data obtained from cycle I to cycle II, it can be concluded, that through environment-based teaching can increase the activity and speaking ability of class V MIN students in South Pariaman Lading.Keywords: Speaking ability, Motivation, environment-based teaching